Informal Learning and Indigenous Intellectuals in New Spain: the Case of Domingo Chimalpahin (1579-after 1640) - Arenas-Pacheco, Carlos Diego (2025)
Using the modern distinction between formal and informal education, this history of education article proposes some avenues of informal learning that Indigenous intellectuals in colonial Mexico pursued outside of formal schooling. Domingo Chimalpahin (1579-after 1640), the most productive Nahuatl-language writer and historian in colonial Mexico, is a clear and relevant case study. Since we lack much of Chimalpahin’s biographical data, previous research has suggested that elucidating specific details about his education can contribute to a better interpretation of his writings and a deeper understanding of the education of non-formally schooled Indigenous intellectuals in colonial Mexico. While it is hypothesized that Chimalpahin had at least basic formal schooling, this article argues that informal learning, in the form of (1) intergenerational learning, (2) work-related learning, and (3) intellectual networking, provided Chimalpahin with the education he needed to craft his works.